Childhood Abuse and Inflammatory Responses to Daily Stressors - Gouin, Jean-Philippe (2012)
BACKGROUND: Childhood abuse leads to greater morbidity and mortality in adulthood. Dysregulated physiological stress responses may underlie the greater health risk among abused individuals. PURPOSE: This study evaluated the impact of childhood abuse on inflammatory responses to naturalistically occurring daily stressors. METHODS: In this cross-sectional study of 130 older adults, recent daily stressors and childhood abuse history were evaluated using the Daily Inventory of Stressful Events and the Childhood Trauma Questionnaire. Blood samples provided data on circulating interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and C-reactive protein (CRP). RESULTS: Childhood abuse history moderated IL-6 levels, but not TNF-α and CRP responses to daily stressors. Individuals with a childhood abuse history who experienced multiple stressors in the past 24 hours had IL-6 levels 2.35 times greater than those of participants who reported multiple daily stressors but no early abuse history. CONCLUSION: Childhood abuse substantially enhances IL-6 responses to daily stressors in adulthood.